Italian adaptation of the Edinburgh Social Cognition Test (ESCoT): A new tool for the assessment of theory of mind and social norm understanding - Isernia, Sara; MacPherson, Sarah E.; Baksh, R. Asaad; Bergsland, Niels; Marchetti, Antonella; Baglio, Francesca; Massaro, Davide (Frontiers in Psychology, 2022)
The relevance of social cognition assessment has been formally described in the Diagnostic and Statistical Manual of Mental Disorders-5. However, social cognition tools evaluating different socio-cognitive components for Italian-speaking populations are lacking. The Edinburgh Social Cognition Test (ESCoT) is a new social cognition measure that uses animations of everyday social interactions to assess (i) cognitive theory of mind, (ii) affective theory of mind, (iii) interpersonal social norm understanding, and (iv) intrapersonal social norm understanding. Previous studies have shown that the ESCoT is a sensitive measure of social cognition in healthy and clinical populations in the United Kingdom. This work aimed to adapt and validate the ESCoT in an Italian population of healthy adults. A translation-back-translation procedure was followed to create and refine the Italian version. Then, 94 healthy adults (47 females, Mage= 35±15.9) completed the ESCoT, a battery of conventional social cognition tests (Yoni; Reading the Mind in the Eyes, RME; Strange Stories, and Social Norm Questionnaire, SNQ) and measures of intelligence and executive functions. Reliability, convergent validity, and predictors of performance on the ESCoT were examined. Results demonstrated good reliability of the ESCoT and an association between the ESCoT scores and some traditional social cognition tests (Yoni cognitive subscale, SNQ). Hierarchical regression results showed that the ESCoT total score was associated with age. Also, the ESCoT subscore (intrapersonal social norm understanding) was associated with education. These findings support the ESCoT as a valid tool testing social norm understanding, a reliable measure of social cognition for an adult Italian population, and provides further evidence that the ESCoT is sensitive to age- and education-related changes in social cognition, and it is a task not affected by general cognitive functioning.